2021
DOI: 10.1057/s41599-021-00752-7
|View full text |Cite
|
Sign up to set email alerts
|

How shades of truth and age affect responses to COVID-19 (Mis)information: randomized survey experiment among WhatsApp users in UK and Brazil

Abstract: We examined how age and exposure to different types of COVID-19 (mis)information affect misinformation beliefs, perceived credibility of the message and intention-to-share it on WhatsApp. Through two mixed-design online experiments in the UK and Brazil (total N = 1454) we first randomly exposed adult WhatsApp users to full misinformation, partial misinformation, or full truth about the therapeutic powers of garlic to cure COVID-19. We then exposed all participants to corrective information from the World Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
3
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 51 publications
6
52
3
10
Order By: Relevance
“…Following Vijaykumar et al, we divided participants into an older group (> 55 years old) and a younger group (< 56 years old). Overall, older participants had lower baseline agreement for myths than younger people, consistent with Vijaykumar et al (44), although correction was effective for all formats and no back re effects were observed (44). Analysis of older and younger participants separately showed that while younger participants showed the same correction format effects as those of the main analysis, older participants showed no differences.…”
Section: Exploratory Questionssupporting
confidence: 82%
See 3 more Smart Citations
“…Following Vijaykumar et al, we divided participants into an older group (> 55 years old) and a younger group (< 56 years old). Overall, older participants had lower baseline agreement for myths than younger people, consistent with Vijaykumar et al (44), although correction was effective for all formats and no back re effects were observed (44). Analysis of older and younger participants separately showed that while younger participants showed the same correction format effects as those of the main analysis, older participants showed no differences.…”
Section: Exploratory Questionssupporting
confidence: 82%
“…Misinformation researchers have sometimes observed "back re" effects, whereby attempted correction leads to elevated belief in the myths (38,(60)(61)(62). While such effects have not been consistent in mythbusting research (30,31,36,43), back re was recently observed for older people when attempting to correct a COVID-19 myth about garlic (44) in a similar study to ours. We found that common COVID-19 correction formats did not cause back re effects, even in older people.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Another study found that those with older age may be more vulnerable to misinformation due to decline in cognitive function and abstract reasoning [28]. Our study also shows that YouTube is also almost as widely used as WhatsApp.…”
Section: Discussionsupporting
confidence: 63%